APPLICATIONS OF PASSIVE ORGANIC TRACK DETECTOR IN NUCLEAR, MATERIAL AND ENVIRONMENTAL SCIENCES - Baykara, Oktay; Dogru, Mahmut (Nova Science Publishers, Inc, 2010)
Track detectors were discovered by Young, Silk and Barner, and they have been widely used in science and technology. Detection technique based on using track detectors and presently called solid state nuclear track detection (SSNTD). The various types of passive track detectors, for example CR-39, LR 115, DNC and Makrofol E have different etching technique and maximum detectable energy ranges of alpha particles, carried out in large number of fields involving different aspect of nuclear, material and environmental science. Briefly, some of these fields are archeology, cosmology, biophysics, particle physics (e.g., exotic phenomena), geochronology, seismology (e.g., earthquake prediction), metallurgy, nuclear physics and medical studies. This technique used in all above various fields based on detection of charged particles with solid state track detectors. Shortly, this chapter condenses on the applications of this technique in the various scientific areas.
Keywords: Organic track detector; radiation detection; science; technology